SISTEM INFORMASI KEARSIPAN DOKUMEN SURAT JALAN BERBASIS WEB PADA PT OLAK KEMANG - Riza Syahrial; Djanuri Djanuri; Dwi Rizkyana (JRIS : Jurnal Rekayasa Informasi Swadharma, 2021)
PT Olak Kemang is a company engaged in the field of freight forwarders and customs clearance. This company is one of the growing forwarder companies in Indonesia. Although the company is still developing, the company's documents are well organized and managed. One of the important sub-sections that require a document filing system at PT Olak Kemang is the travel document sub-section. Archive management of travel documents at PT Olak Kemang is still manual and stored in a special archive rack, even the softcopy is only found on the operational admin's personal computer, resulting in frequent occurrence of lost or tucked documents. The method used for collecting data or information and facts about materials that have to do with the problem to be discussed, is carried out by conducting field research with observation and interview data collection techniques. Therefore, a proposal was made on web-based document archiving to facilitate the management of PT Olak Kemang document archives